2020
DOI: 10.5539/jel.v9n6p59
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Demand for Education in Saudi Arabia: How Effective Is Borrowing Educational Models from the West?

Abstract: The Kingdom of Saudi Arabia (KSA) considers education a top priority, and more emphasis has been placed on this following the 2016 announcement of Saudi Vision 2030. Since then, the country has witnessed several economic and social changes. As a result, the Kingdom has initiated a plan to invest in human capital through education to diversify its economy and increase employment. This includes educational reform with regard to primary and secondary education geared toward preparing students for higher education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In countries going through significant developmental changes, incidence rates have a tendency to rise, along with rising HDI, indicating a strong correlation [1]. Between 1999 and 2018, Saudi Arabia's HDI value increased by 22.8% [37]. The CRC incidence has been rising rapidly in nations going through a significant economic transformation and embracing a Western lifestyle [38].…”
Section: Discussionmentioning
confidence: 99%
“…In countries going through significant developmental changes, incidence rates have a tendency to rise, along with rising HDI, indicating a strong correlation [1]. Between 1999 and 2018, Saudi Arabia's HDI value increased by 22.8% [37]. The CRC incidence has been rising rapidly in nations going through a significant economic transformation and embracing a Western lifestyle [38].…”
Section: Discussionmentioning
confidence: 99%
“…1. For further insights into IEF in Saudi Arabia, readers may refer to the works of Belouafi et al(2012), Mirghani (2020), Hamdan (2015) and Smith & Abouammoh (2013). …”
Section: Notementioning
confidence: 99%
“…The Kingdom of Saudi Arabia (KSA) has the highest number of students enrolled in higher education among the Gulf Cooperation Council countries. To reduce its high youth unemployment rate, Saudi Arabia aims to diversify its economy beyond oil, following the announcement of Saudi Vision 2030 (Mirghani, 2020). By 2030, Saudi Arabia aims to boost its non-oil exports from 16% to 50% of its GDP.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have demonstrated that the academic performance of students is a prime parameter for assessing education quality. Corroborating this view, Mirghani (2020) contends that the academic achievement of students is a major indicator of quality education. Likewise, educationists like Cabrera and Torres (2021) postulated that academic achievement is a significant indicator of quality education and a successful future.…”
Section: Introductionmentioning
confidence: 99%